A Smart Flexible Solid State Photovoltaic Device with Interfacial Cooling Recovery Feature through Thermoreversible Polymer Gel Electrolyte. Issue 36 (9th August 2018) - Sonigara, Keval K.; Machhi, Hiren K.; Vaghasiya, Jayraj V.; Gibaud, Alain; Tan, Swee Ching; Soni, Saurabh S.
Abstract: Quasi‐solid‐state dye‐sensitized solar cells (DSSCs) fabricated with lightweight flexible substrates have a great potential in wearable electronic devices for in situ powering. However, the poor lifespan of these DSSCs limits their practical application. Strong mechanical stresses involved in practical applications cause breakage of the electrode/electrolyte interface in the DSSCs greatly affecting their performance and lifetime. Here, a mechanically robust, low‐cost, long‐lasting, and environment‐friendly quasi‐solid‐state DSSC using a smart thermoreversible water‐based polymer gel electrolyte with self‐healing characteristics at a low temperature (below 0 °C) is demonstrated. When the performance of the flexible DSSC is hindered by strong mechanical stresses (i.e., from multiple bending/twisting/shrinking actions), a simple cooling treatment can regenerate the electrode/electrolyte interface and recover the performance close to the initial level. A performance recovery as high as 94% is proven possible even after 300 cycles of 90° bending. To the best of our knowledge, this is the first aqueous DSSC device with self‐healing behavior, using a smart thermoreversible polymer gel electrolyte, which provides a new perspective in flexible wearable solid‐state photovoltaic devices. Abstract : Wearable electronic devices demand strong bearing power against the multiple bending for their greater life span. A smart aqueous polymer gel electrolyte enabled flexible photovoltaic device with unique self‐healing characteristics is represented here. At a lower temperature, the thermoreversible behavior of the gel electrolyte revives the electrode/electrolyte interface in the flexible device which is damaged due to multiple bending, stretching and twisting actions.